Going Beyond the “Synthetic Method”: New Paradigms Cross-Fertilizing Robotics and Cognitive Neuroscience - Datteri, Edoardo; Chaminade, Thierry; Romano, Donato (Frontiers in Psychology, 2022)
In so-called ethorobotics and robot-supported social cognitive neuroscience, robots are used as scientific tools for the study of animal behaviour and cognition. Building on previous epistemological analyses of biorobotics, in this article it is argued that these two research fields - ethorobotics and robot-supported social cognitive neuroscience -, widely differing from one another in the kinds of robots involved and in the research questions addressed, share a common methodology, which significantly differs from the “synthetic method” that dominated biorobotic approaches to the study of animal (including human) behaviour until recently. The methodological novelty of this strategy, the research opportunities that it opens, and the theoretical and technological challenges that it gives rise to, will be discussed with reference to the peculiarities of the two research fields. Some broad methodological issues concerning the generalization of results concerning robot-animal interaction to theoretical conclusions on animal-animal interaction will be identified and discussed.